Financial markets and the macroeconomy : a Keynesian perspective - Chiarella, Carl. (Abingdon, Oxon ; New York, NY : Routledge, 2009)
The book takes Keynesian theoretical perspective, representing an attempt to revive what Keynes stressed in his General Theory, namely the role of financial market in macroeconomic outcomes.
Price dynamics and the macroeconomy -- Stock market and the macroeconomy -- Bond market, term structure, and the macroeconomy -- Financial markets in open economies -- Stock market and exchange rates -- Output and stock market dynamics with state-dependent financial market reactions -- Real-financial market interaction : implications of budget equations and capital accumulation -- A stochastic model of the real financial interaction with boundedly rational heterogeneous agents -- A high-dimensional model of real financial market interaction : the cascade of stable matrices approach -- Stock market, interest rate, and output : a model and estimation for US Time series data -- Capital account and government budget dynamics in perfect open economies -- Twin deficits and inflation in the Mundell-Fleming-Tobin model -- Financial crisis, currency crisis, and large output loss -- Emerging market economies, currency crisis, and price level adjustment -- Outlook : international capital flows in the MFT approach.
Includes bibliographical references.
rpm 08/05/13
Loans
Keywords: Money market; Macroeconomics; Keynesian economics; Keynes, John Maynard, -- 1883-1946.